Molecular Context of ADP-ribosylation in Schistosomes for Drug Discovery and Vaccine Development - Chutshela, Amandla; Masamba, Priscilla; Oyinloye, Babatunji E.; Kappo, Abidemi Paul (Current Drug Discovery Technologies, 2021)
Schistosome infection is regarded as one of the most important and neglected tropical diseases associated with poor sanitation. Like other living organisms, schistosomes employ multiple biological processes, of which some are regulated by a post-translational modification called Adenosine Diphosphate-ribosylation (ADP-ribosylation), catalyzed by ADP-ribosyltransferases. ADP-ribosylation is the addition of ADP-ribose moieties from Nicotinamide Adenine Dinucleotide (NAD+) to various targets, which include proteins and nucleotides. It is crucial in biological processes such as DNA repair, apoptosis, carbohydrate metabolism and catabolism. In the absence of a vaccine against schistosomiasis, this becomes a promising pathway in the identification of drug targets against various forms of this infection. The tegument of the worm is an encouraging immunogenic target for anti-schistosomal vaccine development. Vaccinology, molecular modeling and target-based drug discovery strategies have been used for years in drug discovery and for vaccine development. In this paper, we outline ADP-ribosylation and other different approaches to drug discovery and vaccine development against schistosomiasis.
Keywords: Sm14